De la sociabilité au genre et à la sexualité. Entretien avec Michel Bozon sur les étapes d’un parcours sociologique - Michel Bozon; Baptiste Coulmont; Marianne Blidon (Genre, Sexualité et Société)
In this interview Michel Bozon revisits his intellectual and academic training by broadly defining it in the field of sociology. The encounters and friendships that have structured and guided him throughout his methodological choices are evoked. From the ENS where he discovered anthropology, to his discovery of fieldwork after having joined the INED as a sociologist, where he undertook the study of large scale populations, a pattern in his choices of research become a theme; sociability and urban reproduction to pair the formation and maintenance of gender inequalities in the context of sexuality. He demonstrates the fruitfulness of an approach that does not oppose politics, theory, or the production of empirical data. Finally, in an example that compares France and Brazil, he presents the argument that while gender asymmetries are universal, they are not produced through the same channels or internalized in the same fashion. This in turn demonstrates that there is no physical sexuality that has never been included in the interpretation, both in meaning and in the social history, of a country.